2009
DOI: 10.1089/jwh.2008.1309
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Beliefs, Barriers, and Enablers among Postpartum Women

Abstract: A number of barriers and enablers were identified for physical activity, most of which were consistent at 3 and 12 months postpartum. This study provides information to create more successful interventions to help women be physically active postpartum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
155
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(182 citation statements)
references
References 48 publications
20
155
1
2
Order By: Relevance
“…This is consistent with sociological evidence that women do the lion share of young infants' care, which reduces the time that they can devote to leisure -including activities that feature MVPA (Craig 2007). Other potential reasons include a higher post-partum prevalence of overweight, tiredness and mobility restrictions amongst women (Evenson et al 2009). Second, the pattern of change in the frequency of MVPA differs by sex across the transition to parenthood: women experience a smooth declining trend before and after the birth of the first child, whereas men experience an abrupt fall in the year immediately after.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with sociological evidence that women do the lion share of young infants' care, which reduces the time that they can devote to leisure -including activities that feature MVPA (Craig 2007). Other potential reasons include a higher post-partum prevalence of overweight, tiredness and mobility restrictions amongst women (Evenson et al 2009). Second, the pattern of change in the frequency of MVPA differs by sex across the transition to parenthood: women experience a smooth declining trend before and after the birth of the first child, whereas men experience an abrupt fall in the year immediately after.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers report barriers to regular exercise, such as lack of time due to care-giving, household and work responsibilities, no one with whom to exercise (a lack of social support), lack of child-care, and poor health (Evenson, Aytur, & Borodulin, 2009;Albright, Maddock, & Nigg, 2005;Pereira et al, 2007). Many of these barriers, particularly isolation and lack of time, are also components of general parenting stress (Williford, Calkins, & Keane, 2007;Horowitz & Damato, 1999;George, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a study by Evenson et al [38], very low moderate activity was reported at 12-month postpartum. Similar to Kulkarni et al [39], we also found no significant change in the percent lean mass although their longitudinal study was performed on low-income group of Indian mothers.…”
Section: Discussionmentioning
confidence: 64%